2019
DOI: 10.1016/j.ecolind.2019.105649
|View full text |Cite
|
Sign up to set email alerts
|

A simple biodiversity assessment scheme supporting nature-friendly farm management

Abstract: Farmers are important actors for regional development and biodiversity protection. Agri-environment-climate measures (AECM) are therefore a central tool of the European Union to support its biodiversity conservation policy. AECM generally reward farmers for fulfilling predefined management actions or avoiding specific practices. In contrast, result oriented AECM are intended to reward farmers for the outcome of nature friendly management practices. This approach gives more flexibility in management and hence p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…For example, Alam et al (2020) assessed fish biodiversity in Korean 'rivers' using eDNA metabarcoding approaches. Soil components were mentioned secondmost commonly (Drummond et al, 2015;Tasser et al, 2019;Nørgaard et al, 2021), followed by geological components (Coops et al, 2009;Kitching and Ashton, 2013;Lindqvist et al, 2016), and geomorphological components (Reyers et al, 2007;Mohapatra et al, 2019;Ge et al, 2021). Biodiversity assessments infrequently mentioned all definition components (Gioia and Pigott, 2000;Burke et al, 2008;Coops et al, 2009;Graham et al, 2010;Sosa et al, 2014;Gatti and Notarnicola, 2018), with most cases before 2010, supporting the above increasing trending value in recent years (Figure 1).…”
Section: Geodiversity Inclusiveness In Biodiversity Assessmentmentioning
confidence: 74%
“…For example, Alam et al (2020) assessed fish biodiversity in Korean 'rivers' using eDNA metabarcoding approaches. Soil components were mentioned secondmost commonly (Drummond et al, 2015;Tasser et al, 2019;Nørgaard et al, 2021), followed by geological components (Coops et al, 2009;Kitching and Ashton, 2013;Lindqvist et al, 2016), and geomorphological components (Reyers et al, 2007;Mohapatra et al, 2019;Ge et al, 2021). Biodiversity assessments infrequently mentioned all definition components (Gioia and Pigott, 2000;Burke et al, 2008;Coops et al, 2009;Graham et al, 2010;Sosa et al, 2014;Gatti and Notarnicola, 2018), with most cases before 2010, supporting the above increasing trending value in recent years (Figure 1).…”
Section: Geodiversity Inclusiveness In Biodiversity Assessmentmentioning
confidence: 74%
“…Regarding biodiversity management of grassland for increased species diversity, one fifth of the interviewed farmers stated that their current practices are, in their opinion, well adapted for good biodiversity management. On some of the farmers' grasslands, this statement was supported by results from surveys of plant and animal species richness, which often confirmed that these famers implemented measures to enhance species richness [43]. Many others mentioned moving towards extensive management during the last decade, although one quarter of farmers stated no change in practices.…”
Section: Good Pastures Good Meadows and Biodiversity Managementmentioning
confidence: 84%
“…Based on this study, emphasise the need for farmers to receive extensive training in order to carry out the data collection in such an assessment scheme, and potentially, for some aspects of the data collection to be done by professionals. Tasser, E., Rüdisser, J., Plaikner, M., Wezel, A., Stöckli, S., Vincent, A., Nitsch, H., Dubbert, M., Moos, V., Walde, J. and Bogner, D., 2019 2020) detail a citizen science project developed specifically for their study, in which data collection was carried out by volunteers with existing specialist knowledge, on farms across Michigan. There is no mention of farmer involvement in data collection, although presumably there was some communication with farmers in order to set up the study.…”
Section: Birds On Farms (Australia)mentioning
confidence: 99%
“…and Jiguet, F., 2012. Mapping from heterogeneous biodiversity monitoring data sources. Biodiversity and Conservation,21(11) Tasser, E., Rüdisser, J., Plaikner, M., Wezel, A., Stöckli, S., Vincent, A., Nitsch, H., Dubbert, M., Moos, V., Walde, J. and Bogner, D., 2019…”
Section: National Odonatology Surveymentioning
confidence: 99%